The Role of Profitability in Moderating the Influence of Sustainability Reporting and ESG Disclosure on Firm Value in Local Publicly-Owned Enterprises in Bogor City - Aprillia Purwanti; Immas Nurhayati; Abrista Devi (Universitas Ibn Khladun Bogor, 2026)
The results of this study indicate that ESG Disclosure and Sustainability Reporting have a significant effect on firm value. Meanwhile, profitability, proxied by Return on Assets (ROA), does not have a significant effect on firm value, proxied by Ln Asset. The results of the moderation test indicate that profitability is unable to moderate the relationship between ESG Disclosure and firm value, while the results of the moderation test on Sustainability Reporting show a significant positive effect. Simultaneously, all independent variables and interaction variables have a significant effect on firm value with a Prob (F-statistic) value of 0.000. The Adjusted R-Squared value of 0.764670 indicates that the variables in the study are able to explain 76.46% of firm value. This research is expected to be a reference for companies in improving the quality of ESG disclosure and Sustainability Reporting to increase firm value.